Interpretative Phenomenological Analysis of Hate Speech among Editors of Daily Trust, The Nation and The Guardian Newspapers in Nigeria - Aondover Eric Msughter (Budapest International Research and Critics University, 2022)
All over the world, hate speech represents a form of threat to damage the lives of individuals and increase the sense of fear in entire communities. Scholars have aligned with the description that it is a globally-endorsed paradigm that the press as an important institution in the democratic process plays a key role during elections. As the Fourth Estate of the Realm, the press provides the platform for narratives and discourses in the service of elections, political negotiations, and other features of the contestations among politicians and other civil organisations involved in election administration. However, problems associated with election reporting and media role in political contestations and machinations, particularly on the African continent, have been a recurrent clog in the wheel of politics in Africa. For instance, in Nigeria, since the 1950s up to the early 1980s, spiraling into the Fourth Republic that started in 1999 and beyond, several election problems that were rooted in perceived mishandling of the electoral process by the media has occurred in the country. The 1965 parliamentary and 1983 general elections were faced by conflicts with accompanying widespread violence, which resulted in military interventions. Within this context, the study adopts an interpretative phenomenological analysis with editors of Daily Trust, The Nation, and The Guardian newspapers in relation to the reportage of the 2015 and 2019 general elections in Nigeria. The theoretical tenets of Critical Race Theory serve the study goal. Nine Editors were purposively selected for an in-depth interview. Arising from the interview, the study discovered that there are implications of hate speech on the professional journalistic practice as it undermines the ethics of the journalism profession. The study recommends that as gatekeepers of the content, editors should engage in checking and cross-checking of facts as a guiding principle in the professional journalistic practice in Nigeria.